Efficiency, socio-economic factors and market analyses of hydropower industry in the EU region - Oluwaseyi, Zubair Azeem (2020)
The hydropower industry is a crucial catalyst for improving the European Union’s National Renewable Energy Action Plan (NREAP), energy efficiency, and mitigation of greenhouse gas (GHG) emissions. Meanwhile, the hydropower industry's deteriorating status, from conventional to marginal renewable technology, is currently struggling head-on with other sustainable energy sources. Several factors are causing the struggle; the installed capacity cost of the EU hydropower industry is high compared with other key countries or regions, lack of additional installed capacity in many EU countries, policy and public support, among others. The thesis, therefore, builds on secondary data from 26 European Union (EU) member countries from the World Development Indicators (WDI), Food and Agriculture Organization of the United Nations statistics (FAOSTAT), European Union statistics (Eurostat), Organization for Economic Co-operation and Development (OECD), Economic Policy Uncertainty (EPU), and AQUASTAT. The dataset for this research covers the period from 1990-2018. Throughout the empirical sections, we divided the EU26 member countries into EU15 (developed) & EU11 (developing) countries. The first objective investigates the hydropower industry's cost efficiency and the role of socio-economic factors on cost efficiency in the EU region. This is a two-stage analysis where the first stage calculates the cost efficiency (CE) and its decomposition, i.e., technical efficiency (TE) and allocative efficiency (AE), using a multi-stage approach of data envelopment analysis (DEA). The second stage investigates socio-economic factors on cost efficiency, using the Fixed Effect (FE) model. The first stage result indicates a cost inefficiency level in the EU hydropower industry due to technical inefficiency. The fixed effects results reveal that capital, research & development (R&D), and total renewable electricity output played a positive and significant role in improving cost-efficiency. Moreover, regulatory uncertainty plays a deleterious impact on the hydropower industry's cost efficiency in the EU region over the study period. The second objective investigates the hydropower industry's technical efficiency and the role of socio-economic factors on technical efficiency in the EU region. This is a two-stage analysis where the first stage calculates the technical efficiency (TE) and its decomposition, i.e., pure-technical efficiency (PTE) and scale efficiency (SE), using a multi-stage data envelopment analysis (DEA) techniques. On the other hand, the second stage investigates socio-economic factors on technical efficiency, using the panel data approach of the Random Effects (FE) model. Results showed that the technical efficiency level is weak due to weak pure-technical efficiency. The panel model outcomes unravel that economic growth, capital and research & development played a positive and significant role in the hydropower industry's technical efficiency. However, regulatory uncertainty and temperature change significantly reduced the hydropower industry's technical efficiency in the EU region. The third objective analysed the drivers and forecasted the hydropower industry market in the EU region, using the two-stage least square (2SLS) and autoregressive integrated moving average (ARIMA) models. The supply side's analytical results, input resource, and price are positive hydropower drivers, while high input cost significantly reduced them. As for the demand side, findings show that hydropower's price is negative and significantly reduced demand. Substitute price and income are positive drivers of hydropower demand in the EU region. The forecasted market results demonstrate that supply would variably be enough to cater to hydropower demand in the European Union region until 2030. There is indisputable evidence of slow technological progress for the hydropower industry in the EU region; thus, innovative initiatives focused on hydropower generating technology are needed. Regulators should make clear and be consistent with the requirements for investing in hydropower. The EU hydropower regulators should encourage the inefficient hydropower industry to use efficient ones to benchmark cost efficiency improvement. Besides, the industry is also faceted with a managerial challenge, pointing to more technical knowledge is needed. Therefore, an organisational strategy (PTE) that emphasises improvements in hydropower's installed capacity should be encouraged. It is also essential to define and prioritise extended-term investment plans for flexible hydropower facilities, especially in EU countries, where the technical feasibility of hydro is abundant. The climate change adaptation framework of COP21 should be preserved, so the negative impact of temperature change on hydropower's technical efficiency could be minimized. It would be beneficial if the EU could make the transmission grid of hydropower a national project, so hydropower can easily accessible for consumption, thus avoiding waste in electricity generations.